Estudo da imobilização de lipase tipo B de candida antarctica utilizando fibra da casca de coco verde como suporte - Brígida, Ana Iraidy Santa (2006)
For the last few years, many researches have sought for inexpensive support matrixes to enzyme immobilization. Meanwhile, in Brazil, an effort is being made to find alternative uses to green coconut husk, an agroindustrial waste. Therefore, the present study investigates the feasibility of using green coconut fiber for the immobilization of Candida antarctica lipase B. Two immobilization strategies were investigated: adsorption and covalent attachment. The effect of different variables on adsorption process have been studied, such as: lipase loading, contact time, pH of the coupling media and pH of the support surface. A stable immobilized enzyme was obtained by contacting coconut fiber washed with water (surface pH = 5) with an enzyme solution containing 40 U/mL in sodium phosphate buffer (pH 7.0) for 2h at room temperature. The thermal stabilization factor at 60ºC was 92.15. Kinetic parameters for Michaelis-Menten model (Km and Vmáx) were the same for both immobilized enzyme and soluble enzyme. It was also observed that coconut fiber is an ion exchange material because of the influence of the coupling media pH on adsorption. Afterwards, we have studied the effect of some variables on the covalent immobilization on coconut fiber activated with GPTMS, such as: lipase loading, contact time, pH of the coupling media, use of additives during the immobilization and sodium borohydride as reducing agent of the Schiff’s bases formed on the covalent attachment. It was observed that a high enzyme loading, for instance 280 U/mL of initial enzyme concentration on the supernatant, promoted a multilayer immobilization. The effect of butyric acid and PEG 6.000, both used as additives during immobilization, were not significant on hydrolytic activity or butyric acid conversion. The use of sodium borohydride as a reducing agent of the Schiff’s bases promoted a loss on the immobilized enzyme activity. Moreover, the immobilized enzyme obtained after the reduction was less stable considering thermal stability in all the cases studied. Best results of enzyme loading, operational stability of synthesis and storage stability were obtained when the enzyme was immobilized covalently at pH 7. Drawing a comparison between adsorption and covalent attachment, results allow concluding that, for aqueous media reactions, the use of immobilized enzyme by covalent attachment is more indicated. However, the immobilization by adsorption a suitable method for organic media reactions, since it is cheaper and a very stable immobilized enzyme is obtained. Finally, searching to increase the surface area of the support and to characterize it, somo studies have been made on the fiber morphologic characteristics and on its modifications after each treatment.